Assistance in the Management of Village Owned Enterprises (Bumdes) in Lapeo Village, Polewali Mandar Regency - Andi Nur Fiqhi Utami; M. Paharuddin; Aco Nata Saputra; Riady Ibnu Khaldun; Muhammad Tanzil Aziz Rahimallah (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this community service is to provide assistance related to the Management of Village Owned Enterprises (BUMDes) in Lapeo Village. Based on the research results the main factors that determine the successful implementation of the BUMDes Management strategy are village policy support, community participation, and also the ability of managers. For more details related to the BUMDes Problem Analysis in Menara Paindo are as follows: 1) The performance of BUMDes management is not optimal; 2) BUMDes Menara Paindo which has just had the status of a legal entity; 3) The lack of exploration of potential business fields; 4) Low public understanding of the roles and functions of BUMDes; 5) Low support from district and provincial governments.